(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
This article is devoted to the substantiation of the need to teach terminal vocabulary and the development of its methodology in higher educational institutions. The goal of the article is that in the system of higher education, attaching importance to the problems of teaching professional terminology, to develop a methodology for their effective teaching, which will improve the process of mastering terminal vocabulary by students in this specialty. The article attempts to present these problems and indicate ways to effectively provide professional vocabulary in the learning process. Being the fastest growing and changing part of the vocabulary of any language, the problem of teaching scientific words in the system of higher professional education is important and relevant. The scientific novelty of the article proposed by us on the specialization of the ways of the emergence of terminal vocabulary, etymology, spelling is the identification of the problem of consistent and purposeful teaching of spelling, specifics and means of term formation, semantic fields and the indication of effective ways of learning.